Pengaruh Kadar Semen dan Gradasi Agregat pada Campuran Lapis Fondasi Agregat Semen terhadap Kuat Tekan, Kuat Lentur, dan Modulus Elastisitas - Asrie, Betarokhmah Nuriva; Rahman, Harmein; Hariyadi, Eri Susanto (Jurnal Teknik Sipil, 2023)
Cement-treated base (CTB) is an aggregate mixture with relatively low water and cement content for pavement base layers, which can provide a stronger and stiffer base layer and requires a lower thickness than using granular layers but has the potential to form reflective cracks in the surface layer. Therefore, CTB should not be too stiff and the compressive strength needs to be limited. The research was carried out to analyze the effect of variations in cement content, gradation, and mix density on compressive strength, flexural strength, and elastic modulus. This research also analyzed the resistance of flexible pavement structures with CTB to asphalt fatigue and permanent deformation failure using the AUSTROADS 2017 method and the CIRCLY 6.0 program. The stiffness of CTB with Bina Marga gradation is built by the aggregate material (initially stiff), while the stiffness of CTB with FAA gradation is built by cement and the aggregate material tends to give flexible behavior because it is easier to move. The results showed that CTB with FAA gradation and 5% cement content resulting in a 7-day compressive strength of 3,28 MPa was stated as the optimum mix combination because it provides better resistance to fatigue and permanent deformation failure.